Strategies for monitoring and training strength and power in elite rugby union players. - Gannon, E. (2015)
Rugby union requires high levels of strength and power in order to support the physical requirements of the game. The competitive structure of rugby union in the English premiership places limitations on the time available for players` physical development. The aim of this thesis was to analyse the scope and magnitude of strength and power adaptation potential, whilst identifying effective training strategies to support physical development in professional rugby union players. Chapter 3 monitored lower limb strength and power during the different phases of a professional season. This study demonstrated moderate beneficial increases in all physical capacities over a full season whilst pre and mid-season training cycles represent the greatest opportunity for strength and power enhancement. Chapter 4 assessed the efficacy of complex training performed during a mid-season performance phase and found meaningful increases in selected measures of power whilst maximum strength was maintained. Chapter 5 assessed the impact of pre-conditioning exercise mode selection (cycling or weightlifting) when designing complex training interventions and reported highly individualised response patterns in measures of lower and upper body performance. Chapter 5 also demonstrated no clear support for the short-term effects of elevated free-testosterone on local and systemic muscle performance. Chapter 6 investigated the effects that manipulating work interval duration has on fast muscle activity and power during high intensity interval training (HIT). This study reported greater accumulative power responses and fast muscle activation in selected muscles when shorter work interval durations were prescribed. In summary, scope for physical development exists in professional rugby union players. Complex training may be an efficient in-season training method for power development. Hormonal response patterns represent unpredictable markers of acute and chronic improvements in local and systemic muscle performance. Finally, the endurance potential of fast muscle groups may benefit from HIT protocols designed with shorter work interval durations.